2018
DOI: 10.3390/toxics6040060
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Toxicity Evaluation of Xanthone Crude Extract on Hypoxic Human Hepatocellular Carcinoma and Zebrafish (Danio rerio) Embryos

Abstract: Xanthone is an organic compound mostly found in mangosteen pericarp and widely known for its anti-proliferating effect on cancer cells. In this study, we evaluated the effects of xanthone crude extract (XCE) and α-mangostin (α-MG) on normoxic and hypoxic human hepatocellular carcinoma (HepG2) cells and their toxicity towards zebrafish embryos. XCE was isolated using a mixture of acetone and water (80:20) and verified via high performance liquid chromatography (HPLC). Both XCE and α-MG showed higher anti-prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…A xanthone from G. mangostana, α-mangostin, has been found to be toxic and teratogenic in zebrafish embryos. …”
Section: Resultsmentioning
confidence: 99%
“…A xanthone from G. mangostana, α-mangostin, has been found to be toxic and teratogenic in zebrafish embryos. …”
Section: Resultsmentioning
confidence: 99%
“…This finding is in line with the research result conducted by Jose et al (2016), which reported the occurrence of Growth retardation, movement abnormalities, and, malformation of zebrafish embryos head after exposure to mangosteen leaves and stem-bark lyophilized water extract. In addition, research conducted by Fazry et al (2018) also showed the presence of a bent tail in the zebrafish embryos treated with α-mangostin. This indicates that some of the components contained in mangosteen pericarp or other parts of the plant could cause different effects on the embryonic development of different fish species.…”
Section: Effects Of Mangosteen (G Mangostana) Pericarp Simplicia On L...mentioning
confidence: 94%
“…From the egg phase, zebrafish embryos can survive by ingesting yolk and can visibly be tested for malformation for a few days in a single well of a microplate [ 32 ]. When the embryo is not clumped, has a cardiac beat, has fully shaped body sections, and the tail is detached from the yolk, the standard endpoints of embryogenesis have been said to have occurred [ 28 ]. The main characteristics of embryogenesis and the genetic basis of growth in zebrafish have been widely researched [ 125 ].…”
Section: Using Zebrafish Embryos To Detect Developmental Toxicitymentioning
confidence: 99%
“…One of the endpoints of embryonic growth in zebrafish is when the tail is detached entirely from the yolk [ 28 ], which can be affected by toxicants. The tail emerges during the larval stages from the primordium in the ventral fin fold, which coincides with a gap in the melanophore line immediately before the back tip of the notochord [ 149 ].…”
Section: Defects In Zebrafish Organs Found In Developmental Toxicimentioning
confidence: 99%
See 1 more Smart Citation